Muznost i dijelovi krivulje protoka mlijeka krava Jersey pasmine Milkability and the parts of the milk flow curve of the Jersey cattle breed - Bobić, Tina; Mijić, Pero, agronom; Galinec, Zvonimir; Gregić, Maja; Baban, Mirjana; Mišević, Dijana; Gantner, Vesna (2021)
Cilj rada bio je prikazati neka od osnovnih muznih svojstava te izgled krivulje protoka mlijeka i njezinih sastavnih dijelova kod krava Jersey pasmine. Prosječno trajanje glavne i cijele mužnje iznosilo je 5,99 odnosno 10,13 minuta. Prosječni protok mlijeka iznosio je 2,01, a maksimalni protok mlijeka 3,09 kg/min. Utvrđeno je nešto duže trajanje uzlazne i silazne faze u odnosu na plato fazu krivulje protoka mlijeka. Zabilježena je nešto veća zastupljenost poželjnih krivulja protoka mlijeka koje su dobar indikator zdravlja vimena. Krave s poželjnijim krivuljama mlijeka imale su veću ukupnu količinu pomuženog mlijeka, te veću količinu mlijeka u prvoj, drugoj i trećoj minuti mužnje. Nadalje, utvrđeno je da su krave imale relativno brzo otpuštanje mlijeka, te su unutar jedne minute postizale protok mlijeka od 0,5 kg/min neovisno o izgledu krivulje protoka mlijeka. Nužna su daljnja istraživanja na većem broju grla kako bi se dobili što kvalitetniji zaključci o muznosti krava Jersey pasmine.
The aim of the study was to show some of the basic milking properties and the appearance of the milk flow curve and its components in Jersey cows. The average duration of the main and the whole milking was 5.99 and 10.13minutes, respectively. The average milk flow was 2.01 and the maximum milk flow was 3.09 kg / min. A slightly longer duration of the ascending and descending phases compared to the plateau phase of the milk flow curve was found. A slightly higher prevalence of desirable milk flow curves was recorded, the presence of which is a good indicator of udder health status. Cows with more desirable milk curves had a higher total amount of milk, and a higher amount of milk in the first, second and third minutes of milking. Furthermore, it was found that cows had a relatively fast milk ejection, and within one minute achieved a milk flow of 0.5 kg / min regardless of the appearance of the milk flow curve. Further research is needed on a larger number of animals in order to obtain the best possible conclusions about the milking of Jersey cows.
Bibliografija: 23 jed.
Sažetak ; Summary.
Keywords: Muzne krave -- Jersey pasmina -- Muznost -- Protok mlijeka